Association between pre-diagnostic dietary antioxidant vitamin consumption and ovarian cancer survival: a prospective cohort study. Issue 2 (20th December 2022) - Sun, Ming-Hui; Gong, Ting-Ting; Xu, He-Li; Yin, Jia-Li; Yang, Hui-Juan; Zou, Bing-Jie; Chen, Hong-Yu; Du, Zong-Da; Wang, Ran; Yan, Shi; Xu, Jin; Liu, Fang-Hua; et al.
Abstract : Pre-diagnostic higher vitamin C and β-carotene intake was associated with improved ovarian cancer survival. Abstract : Background : Epidemiological evidence regarding the relationship between dietary antioxidant vitamin intake and ovarian cancer (OC) survival is not clear. Herein, we aimed to first evaluate this topic in a prospective cohort study in China. Methods : The present study included participants from the Ovarian Cancer Follow-Up Study, which was a hospital-based prospective cohort study including OC patients who were aged 18 to 79 years during 2015–2020. The information on the intake of antioxidant vitamins, consisting of vitamin A, retinol, α-carotene, β-carotene, vitamin C, and vitamin E, and other diet information was obtained through a 111-item food frequency questionnaire. Deaths were recorded until March 31, 2021. Hazard ratios (HRs) and 95% confidence intervals (CIs) for overall survival were evaluated using Cox proportional hazards models. Results : There were 130 (18.49%) deaths among 703 OC patients during a median 37.19 months follow-up. In the multivariable-adjusted model, the highest tertile of dietary vitamin C (HR = 0.43, 95% CI = 0.25–0.75, P for trend <0.05) and β-carotene intake (HR = 0.52, 95% CI = 0.31–0.87, P for trend <0.05) was inversely associated with the overall survival of OC when compared with the lowest tertile group. Retinol, vitamin A, vitamin E, and α-carotene consumption showed no association with OC survival. Of note is that the multiplicative interaction was identified between vitamin C intake and residual lesions in OC survival ( P for interaction <0.05). Conclusion : Our findings indicate that pre-diagnostic higher vitamin C and β-carotene intake was associated with improved OC survival.